Pelican Island, Trinidad - (:unkn) unknown (Wilsons Limited[Trinidad], 2011)
Pelican Island is an island in the Republic of Trinidad and Tobago. It is one of “The Five Islands” which is really a group of six small islands lying west of Port of Spain in the Gulf of Paria.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Paria, Gulf of (Venezuela and Trinidad and Tobago); Islands--Trinidad and Tobago; Bodies of water--Trinidad and Tobago; [1920]; Five Islands, The